Aplicação de princípios gestálticos no planejamento de estruturas composicionais utilizadas na peça segmentos - Oliveira, Helder Alves de (2014)
This dissertation examines the potential of application of Gestalt Psychology Principles in the planning of compositional structures in the work Segmentos, for symphony orchestra. The Gestalt analysis of musical works accomplished by several autors, such as Meyer (1956), Lerdahl and Jackendoff (1983), and Tenney and Polansky (1980), was used in this dissertation on a prescriptive fashion. The analogies between musical gestures and features of visual objects perception, according to Gestalt Theory, was thought by these autors. In this dissertation, these analogies were counted as musical suggestions to the planning of the work Segmentos, which consists of three movements. For the planning of the musical gestures in the first movement, titled Hábito, and the third movement, titled Pregnância, subjective or qualitative suggestions were employed, i.e., without using mathematical calculations. For the planning of the musical gestures in the second movement, titled Tenere, objective or quantitative suggestions were employed, besides subjective or qualitative suggestions. For this Second movement, a computer software was created in order to generate and segment melodies, according to works of Tenney and Polansky, who applied by calculations the Gestalt principles related with grouping and segregation of perceptual objects. These melodic segments were substantial for the management of musical parameters. It is our intention that this dissertation, which apply some Gestalt principles in the context of musical composition, shall serve as a basis for the conscious planning of musical works and shall be a reference for research in such a way that one can carry out the examination of other applications of Gestalt principles in the planning of musical works.